Portuguese translation and validation of the YQOL – FD (Youth Quality of Life Instrument—Facial Differences) for brazilian adolescents with craniofacial deformities (Bioscience Journal, 2020)
The Youth Quality of Life—Facial Differences (YQOL-FD), validated in the United States in 2005, was developed at the University of Washington by the Seattle Quality of Life Group (SeaQol), to evaluate quality of life of adolescents with facial deformities. Because no Portuguese version exists, the measure was not viable in Brazil. This study aimed to obtain linguistic and psychometric validation of a version of the YQOL-FD in Portuguese. Twenty-five patients with cleft lip and palate and five without facial deformity participated in Traumatology and Maxillofacial Prosthesis Surgery Clinic, School of Dentistry, University of São Paulo. The linguistic validation of the YQOL-FD was carried out by a team consisting of the researcher, as project manager, two native Portuguese-speaking consultants fluent in English, and one native English-speaking consultant fluent in Portuguese. After translation and back-translation, a Portuguese version was obtained, which was applied in a pilot test (n = 10); after the final adjustments the Seattle Quality of Life Group approved the official version of the YQOL-FD in Portuguese. To obtain the psychometric validation, we requested the participation of 20 patients with cleft lip and palate who answered the questionnaire twice in a range of 7 to 15 days. The Cronbach’s alpha test was applied in the 48-item block, showing a high degree of internal consistency (0.949). The Wilcoxon Signal Post Test was applied to verify if the test and retest values were similar; the general agreement was 4/5 = 80%, indicating high reproducibility. It was concluded that the Portuguese version of the YQOL-FD is adequate for evaluating Quality of Life of Brazilian adolescents with craniofacial deformities.